PROFETISME GEREJA ASIA MENANGGAPI FENOMENA IN VITRO FERTILIZATION DALAM TINJAUAN TEOLOGI MORAL KATOLIK - Benedictus Hasan (Aggiornamento, 2023)
The focus of this paper is the elaboration of In Vitro Fertilization and how to respond to it in the light of Catholic moral theology, particularly within the territory of the Asian Catholic Church. The author wants to see how and what basis the Catholic Church uses in response to this phenomenon. This elaboration is then continued by responding in the form of what the Church, especially the Asian Church, should do to respond to this. The method used in this writing is a critical reading of several sources in the form of Church documents, articles on In Vitro Fertilization and several supporting sources. The findings of this paper are that the practice of In Vitro Fertilization in addition to being medically risky for women who do so is also contrary to Catholic moral teachings that put human dignity at the center of its study. The second finding is that the Asian Church is a dialogical Church, so what the Asian Church can strive to respond to is moral dialogue within the framework of moral formation as a concrete form of the Prophetic voice of the Church.